2011
DOI: 10.1371/journal.pone.0015841
|View full text |Cite
|
Sign up to set email alerts
|

Culture Conversion Among HIV Co-Infected Multidrug-Resistant Tuberculosis Patients in Tugela Ferry, South Africa

Abstract: BackgroundLittle is known about the time to sputum culture conversion in MDR-TB patients co-infected with HIV, although such patients have, historically, had poor outcomes. We describe culture conversion rates among MDR-TB patients with and without HIV-co-infection in a TB-endemic, high-HIV prevalent, resource-limited setting.MethodsPatients with culture-proven MDR-TB were treated with a standardized second-line regimen. Sputum cultures were taken monthly and conversion was defined as two negative cultures tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
36
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 14 publications
13
36
1
Order By: Relevance
“…Extremely high rates of primary MDR-TB have been reported from specific parts of KwaZulu-Natal. (19, 20) A high proportion of MDR-TB patients in these areas with high rates of HIV co-infection had no prior history of tuberculosis treatment, in contrast to a recent multi-country study which showed that a history of previous tuberculosis was the strongest risk factor for MDR-TB. (21, 22) It is also important to note that eight patients in our study initially had confirmed drug susceptible tuberculosis and subsequently developed MDR-TB.…”
Section: Discussionmentioning
confidence: 91%
“…Extremely high rates of primary MDR-TB have been reported from specific parts of KwaZulu-Natal. (19, 20) A high proportion of MDR-TB patients in these areas with high rates of HIV co-infection had no prior history of tuberculosis treatment, in contrast to a recent multi-country study which showed that a history of previous tuberculosis was the strongest risk factor for MDR-TB. (21, 22) It is also important to note that eight patients in our study initially had confirmed drug susceptible tuberculosis and subsequently developed MDR-TB.…”
Section: Discussionmentioning
confidence: 91%
“…High rates of culture conversion within the first six months of effective MDR-TB treatment have also been shown in the past [22]. One possible explanation for lower conversion rates later in treatment is that patients who did not convert in the first six months may have been sicker and less likely to experience conversion on any regimen.…”
Section: Discussionmentioning
confidence: 91%
“…The small number of patients with HIV infection may explain our failure to identify HIV infection as a significant covariate. However, other studies have also shown that HIV infection does not appear to have an effect on sputum conversion rates (28)(29)(30).…”
Section: Discussionmentioning
confidence: 93%